Comparison of hard machining procedures on the basis of the amount of the used up coolant and lubricant - Kundrak, Janos (НТУ "ХПИ", 2011)
The application of coolants and lubricants (CL) considerably contributed to the increase of the efficiency of material removal in metal machining procedures. Both the cooling and the lubricating effect reduces the load on the tools, thus facilitates the partition of the material and the formation of a better surface quality. This article seeks to ascertain whether given production task – namely the machining of a hard surface – can be fulfilled with the same accuracy and economic efficiency if using less CL.

Применение хладагентов и смазок вносит значительный вклад в увеличение эффективности удаления металла при механической обработке. Охлаждение и смазочный эффект уменьшают нагрузку на инструмент, таким образом облегчая отделение материала и формирование поверхностного слоя лучшего качества. Эта работа направлена на решение данной задачи производства – а именно, механической обработки поверхности – и может ли она быть выполнена с той же точностью и экономической эффективностью с использованием меньшего количества смазки.
Сравнение процессов чистовой обработки, базирующееся на количестве используемой смазочно-охлаждающей среды
Keywords: coolant; lubricant; material removal; economic efficiency; материалы высокой твердости; хладагент; смазка